Down Set Fight! - Bowers, Chad; Sims, Chris, 1971- (Oni Press, 2024)
"Fearless" Chuck Fairlane was professional football's fastest rising star, but his career came to a screeching halt when he was expelled from the league after goin' HAM and causing the biggest brawl in the history of sports. Years later, Chuck has found peace as a high school football coach, until costumed mascots begin attacking him for seemingly no reason. Before long, Chuck's going to discover that you can't run away from the past - but you can punch it square in the face!